Phase-field modeling of crack growth and mitigation in solid oxide cells. (26th March 2023) - Xue, Fei; Lei, Yinkai; Cheng, Tian-Le; Epting, William K.; Hackett, Gregory; Abernathy, Harry; Wen, You-Hai
Abstract: Fracture and crack growth is one of the main degradation mechanisms in solid oxide cells (SOCs). However, the modeling of crack growth in SOCs is challenging due to their complex microstructures and possible plasticity development within the Ni particles in Ni-based SOC electrodes. In this study, a phase-field fracture model is developed, which incorporates the SOC microstructures and phase-dependent material properties, including yield strength, fracture toughness in the bulk and at the interphase boundaries. The model is employed to study crack initiation and growth under thermal and redox cycling on the hydrogen electrode side of SOCs. The simulation results demonstrate that under thermal cycling, work-zone cracking dominates in electrolyte-supported SOCs with cracks initiated at the triple-phase boundaries, while only minor mechanical degradation occurs in hydrogen-electrode-supported SOCs after hundreds of thermal cycles. Under redox cycling, through-cracking of yttria-stabilized zirconia (YSZ) in the hydrogen electrode and electrolyte layers dominates. The simulation results suggest several crack-mitigation strategies, including decreasing the porosity in the hydrogen electrode support layer and synchronizing thermal strain to balance oxidation strain. Highlights: A phase-field fracture model incorporating the solid oxide cell microstructures is developed. Crack initiation and growth under thermal and redox cycling are simulated. Work-zone cracking and through-cracking of the electrolyte layer are observed in the simulation results. Crack-mitigation strategies are suggested based on the simulation results.